Regulation of the Employment Status of Seafarers - Boris Jerman (Poredbeno Pomorsko Pravo)
This article discusses the specifics of the employment relationship of seafarers who not only perform their obligations on a ship under an employment contract, but also live far away from their permanent residence, with limited contact with their home environment, including their families. In the past, their position was less than envious, since they, as a party in the working relationship, were clearly under the authority of the shipowner and were very poorly informed about their rights. The situation began to improve in recent times, when the legislator and international organisations, such as the International Maritime Organization (ILO), began to adopt legislation to regulate their position. The Maritime Labour Convention, 2006 (MLC, 2006) is of key importance in the legislation that has recently been adopted to improve the position of seafarers. Its greatest value is that it introduces port state control, which means that member states carry out inspections on ships arriving at their ports to ensure that they comply with its provisions. Regardless of the above, the position of seafarers is still far from desirable as shipowners are trying to reduce their operating costs by cutting down on the number of crew members and their benefits. The situation of seafarers should not only be improved with appropriate legislation, but also with its implementation. The main purpose of this article is to point out the specifics of the legal regulation of the position of seafarers, which cannot be regulated by the provisions of general labour law, and to analyse the development of such regulation which began to improve the position of seafarers from the middle of the 19th century. However, it is necessary to highlight that the legal regulation of seafarers is not a new phenomenon, since it is possible to find regulations from as early as the Middle Ages that contained certain provisions that could serve as an example for modern regulations. Another purpose of this article is to point out that different national regulations are based on the same principles of regulating the position of seafarers. With this aim, the position of seafarers in Slovenia, Croatia, and Italy is analysed. The legislations of the three countries are more or less in compliance with the MLC, 2006 and other international conventions, but they differ in their scope, which is influenced by the extent and importance of the maritime sector in their national economies.